Profil Peresepan Penggunaan Obat Antihipertensi Pada Pasien Hipertensi Di Puskesmas Tanjung Pinang Kota Jambi Periode Oktober-Desember Tahun 2024 - Aprilliani, Septi Riski; Supriadi, Supriadi; Sugiarti, Sugiarti (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Hypertension is the second most common reason for patient visits at Puskesmas Tanjung Pinang, Kota Jambi. Drug use is considered rational if patients receive medications according to their clinical needs. One of the factors influencing rational drug use is prescribing patterns. Appropriate prescribing patterns play a crucial role in the success of therapy. This study aims to determine the prescribing patterns of antihypertensive drugs at Puskesmas Tanjung Pinang, Kota Jambi, during the period of October to December 2024. This research used a descriptive quantitative method with a retrospective approach involving a sample of 210 prescription records. Data were obtained from the medical records of hypertensive patients who received antihypertensive prescriptions during the specified period. The collected data included patient characteristics (age, gender), types of prescribed antihypertensive drugs, and combination therapy patterns. Data were analyzed descriptively in terms of frequency distribution and percentages. The results showed that among the 210 prescriptions analyzed, the majority of hypertensive patients were in the age ranges of 45–54 and 55–64 years (31.9%). Most patients were female (68.6%), and the most common occupation was housewives (66.2%). The most frequently prescribed active substance was amlodipine (96.8%), belonging to the calcium channel blocker (CCB) class, which was also the most prescribed drug class (96.8%). The most commonly used type of therapy was monotherapy (96.6%).